The diagnosis and treatment of adrenocortical carcinoma in pregnancy: a case report - Yuanli Zhang; Zeng Yuan; Chunping Qiu; Shuyi Li; Shiqian Zhang; Yan Fang (BMC, 2020)
Abstract Background Pregnancy complicated with adrenocortical carcinoma (ACC) is a sporadic syndrome that is characterized by hypertension, uncontrolled hypokalemia, severe heart failure, premature delivery and other adverse effects. The clinical presentation of adrenocortical carcinoma is vague and nonspecific, it is challenging to identify complications of pregnancy with adrenocortical carcinoma. Here we present a case of adrenocortical carcinoma during pregnancy. We describe how to distinguish secondary hypertension from other conditions and the importance of timely detection and treatment of such patients. Case presentation A 22-year-old woman 30 weeks pregnant was hospitalized with uncontrolled hypertension and hypokalemia. An ultrasound examination of the right adrenal gland revealed a large mass. She underwent transabdominal adrenalectomy, and histopathology from the sample removed revealed an adrenocortical carcinoma. Five days after surgery, the patient had a premature rupture of the fetal membranes and gave birth to a newborn girl via vaginal delivery at 32 weeks of gestation. The newborn was transferred to the neonatal pediatrics ward, and the woman started receiving chemotherapy. Conclusions Pregnancy with adrenocortical carcinoma is a rare condition. This case alerts the obstetricians that analysis of hypertension, hypokalemia, the plasma level and circadian rhythm of plasma cortisol provides a strategy to diagnose adrenocortical carcinoma during pregnancy.